The validation of matrix metalloproteinase-9 mRNA gene expression as a predictor of outcome in patients with metastatic gastric cancer - Batran, Salah-Eddin al-; Hofheinz, Ralf-Dieter (Annals of oncology, 2020)
AbstractBackground. The prognostic role of matrix metalloproteinase-9 (MMP-9) in metastatic gastric cancer has not been validated.Patients and methods. We car
Available online 7 January 2020
Gesehen am 06.12.2018